A jurisdição universal e a redefinição da soberania: Uma aproximação a partir do Estatuto de Roma como marco normativo prevalecente - Fernández-Altamirano, Antony Esmit Franco; Gonzáles- Herrera, Jesús Manuel; Villegas-Paiva, Elky Alexander; Vargas-Chaves, Iván (Revista Direito e Práxis, 2026)
https://doi.org/10.1590/2179-8966/2026/94131i This article aims to analyze how the principle of universal jurisdiction has reshaped the classic notion of state sovereignty, transforming it into a responsibility to prosecute the most serious crimes affecting the international community. It examines its function as a cornerstone of the International Criminal Court’s complementarity system. Using a documentary analysis methodology, doctrinal and jurisprudential sources are studied, including paradigmatic cases such as Lotus, Arancibia Clavel, Lubanga, and Ongwen. The results show an evolution from a territorial sovereignty model to one that prioritizes the protection of universal legal interests, where national courts act as agents of global justice. It is concluded that the effectiveness of international criminal law depends on states, including Peru, assuming a proactive role in the fight against impunity by overcoming their normative gaps and consolidating a decentralized accountability network that strengthens the Rome Statute system.